Chronic pain in patients with the hypermobility type of Ehlers–Danlos syndrome: evidence for generalized hyperalgesia - Rombaut, Lies; Scheper, Mark; De Wandele, Inge; De Vries, Janneke; Meeus, Mira; Malfait, Fransiska; Engelbert, Raoul; Calders, Patrick (Clinical rheumatology, 2015)
Chronic widespread pain is highly present in patients with the Ehlers–Danlos syndrome hypermobility type (EDS-HT), but up to now, evidence for generalized hyperalgesia is lacking. The aim of this study is to investigate whether pressure pain thresholds (PPTs) at both symptomatic and asymptomatic body areas differ in EDS-HT patients compared to healthy subjects. Twenty-three women with EDS-HT and 23 gender- and age-matched healthy controls participated. All subjects marked on Margolis Pain Diagram where they felt pain lasting longer than 24 h in the past 4 weeks. Then, they completed several questionnaires assessing pain cognitions, fatigue, disability, and general health status, in order to take the possible influence of these factors on PPTs into account. Patients also completed a form concerning the type of pain they experienced. Thereupon, a blinded researcher assessed PPTs at 14 body locations on the trunk and extremities. PPTs were compared for the two complete groups. In addition, PPTs of patients and controls who did not report pain in a respective zone were compared. PPTs of the patients were significantly lower compared to those of the control group, also when pain-free samples per zone were compared. The mean (SD) PPT was 2.9 (1.62) kg/cm 2 in the EDS-HT patients and 5.2 (1.88) kg/cm 2 in the controls ( P < 0.001). No confounding factors responsible for the observed differences could be revealed. In half of the patient group, a predominantly neuropathic pain component was likely present. This study provides evidence for the existence of hyperalgesia even in asymptomatic areas (generalized secondary hyperalgesia). The generalized hyperalgesia may represent the involvement of a sensitized central nervous system, which inquires an adapted pain management for this patient group.